El bosque tropical - Cowcher, Helen (New York : Scholastic, 1992)
The animal inhabitants of a rain forest live in peace, until something even more powerful than Jaguar comes to threaten their world.
Translation of: Rain forest.
Accelerated Reader AR
Reading Counts RC
Keywords: Rain forests -- Juvenile fiction; Animals -- Juvenile fiction; Spanish language materials -- Juvenile fiction; Picture books